Reliability and validity of the Thai version of EQ-5D-5L questionnaire on patients with chronic disease - Sonsa-ardjit, Nontapat; Sakthong, Phantipa (Chulalongkorn Medical Journal, 2023)
Background : The EuroQoL Group’s 5-dimension, 5-level (EQ-5D-5L) is a frequently used questionnaire on generic health-related quality of life (HRQoL); however, studies on its psychometric properties in Thailand are rare, especially on patients with chronic diseases. Objective : To evaluate the reliability and validity of the EQ-5D-5L questionnaire on patients with chronic diseases. Research design : Cross-sectional study. Setting : King Chulalongkorn Memorial Hospital. Methods : Four hundred outpatients with chronic disease at King Chulalongkorn Memorial Hospital between July 2014 and February 2015 were surveyed. The psychometric properties of EQ-5D-5L were evaluated in terms of practicality (administration time and ceiling effect), reliability and validity (known-groups validity and convergent validity). Results : The average administration time was less than 2 minutes. The ceiling effect was 14%. Known-groups validity test was confirmed for the following factors: gender, number of medicines taken, disease control and experiencing ADRs. EQ-5D-5L index scores had a positive correlation with all WHOQOL-BREF domains (rho ranged: 0.27 - 0.58) and EQ-VAS (rho = 0.49, all p < 0.01). The intra-class correlation coefficient of EQ-5D-5L was 0.89 and weighted kappa coefficients ranged 0.44 - 0.60 in the five dimensions of EQ-5D-5L. Conclusions : EQ-5D-5L had confirmed reliability and validity on patients with chronic disease.